1973
DOI: 10.1136/bmj.2.5858.101
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Stress in Wives of Patients with Myocardial Infarction

Abstract: In a study of the psychological consequences of myocardial infarction on 65 wives of husbands admitted to a coronary care unit feelings of loss, depression, and guilt were common at the time of infarction. Many wives (38%) found the period of convalescence after discharge very stressful, attributing this to fears of a recurrent infarct and marital tension owing to their husbands' increased irritability and dependency. These anxieties and tensions gradually diminished and at one year after the initial illness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(57 citation statements)
references
References 1 publication
5
51
0
1
Order By: Relevance
“…No significant differences were found between spouse and patient needs. Hentinen (1983) (see also depression and anxiety (Arefjord, Hallaraker, Odd, & Maeland, 1998;Artinian, 1991Artinian, , 1992Bennett & Connell, 1999;Conway, Skelton, O'Rourke, Cay, & Pentland, 1994;Davies, 2000;Hentinen, 1983;Hilbert, 1993;Joekes, Maes, Boersma, & van Elderen, 2005;Kettunen, Solovieva, Laamanen, & Santavirta, 1999;Langeluddecke, Tennant, Fulcher, Barid, & Hughes, 1989;Mayou, Foster, & Williamson, 1978;Moser & Dracup, 2004;O'Farrell, Murray, & Hotz, 2000;Rose, Suls, Green, Lounsbury, & Gordon, 1996;Ruiz, Matthews, Scheier, & Schulz, 2006;Skelton & Dominian, 1973;Stanley & Frantz, 1988;Stern & Pascale, 1979;Suls, Green, Rose, Lounsbury, & Gordon, 1997;Surtees & Miller, 1994a;Thompson & Cordle, 1988). These studies used a wide variety of measures of anxiety, stress and depression preventing amalgamation into overall estimates of severity or prevalence.…”
Section: Section 1: Psychological Impactmentioning
confidence: 94%
See 1 more Smart Citation
“…No significant differences were found between spouse and patient needs. Hentinen (1983) (see also depression and anxiety (Arefjord, Hallaraker, Odd, & Maeland, 1998;Artinian, 1991Artinian, , 1992Bennett & Connell, 1999;Conway, Skelton, O'Rourke, Cay, & Pentland, 1994;Davies, 2000;Hentinen, 1983;Hilbert, 1993;Joekes, Maes, Boersma, & van Elderen, 2005;Kettunen, Solovieva, Laamanen, & Santavirta, 1999;Langeluddecke, Tennant, Fulcher, Barid, & Hughes, 1989;Mayou, Foster, & Williamson, 1978;Moser & Dracup, 2004;O'Farrell, Murray, & Hotz, 2000;Rose, Suls, Green, Lounsbury, & Gordon, 1996;Ruiz, Matthews, Scheier, & Schulz, 2006;Skelton & Dominian, 1973;Stanley & Frantz, 1988;Stern & Pascale, 1979;Suls, Green, Rose, Lounsbury, & Gordon, 1997;Surtees & Miller, 1994a;Thompson & Cordle, 1988). These studies used a wide variety of measures of anxiety, stress and depression preventing amalgamation into overall estimates of severity or prevalence.…”
Section: Section 1: Psychological Impactmentioning
confidence: 94%
“…However, the studies utilising standardised measures report high levels of anxiety and moderate levels of depression during patient hospitalisation. The majority of longitudinal studies have identified that levels of anxiety tend to gradually decrease over the first year after MI although anxiety levels still remain elevated compared to population norms (Arefjord et al, 1998;Artinian, 1991Artinian, , 1992Conway et al, 1994;Joekes et al, 2005;Langeluddecke et al, 1989;Mayou et al, 1978;Rose et al, 1996;Skelton & Dominian, 1973;Surtees & Miller, 1994a).…”
Section: Section 1: Psychological Impactmentioning
confidence: 95%
“…[36][37][38][39][40] The findings also revealed that wives faced multiple stressors such as potential loss of their partner and family disruption during the wives' experience in critical care. [41][42][43][44] Although these studies provided a foundation for studies of symptoms experienced by patients' family members, the results cannot be generalized because of the relatively small sample sizes, predominantly female samples, and the exploratory nature of the research. It was not until the early 1990s that investigators 45 understood that family members in the ICU could potentially have clinically diagnosable psychological conditions.…”
Section: Stressmentioning
confidence: 99%
“…In spite of these dif culties, most couples will have resumed sexual relations after a year (Papadopolous et al, 1980), only some of whom will have been given advice about sexual health. Skelton and Dominian (1973) report that some wives of male MI patients claimed their dif culties in resuming sexual relations would have been lessened had they received more information from the hospital staff treating their husbands. In fact, in a descriptive study of 20 women and 42 men who were sexually active before an MI, the women received less counselling than the men (Hamilton & Seidman, 1993).…”
Section: Coronary Heart Disease and Strokementioning
confidence: 95%